1996
DOI: 10.1046/j.1365-2141.1996.d01-1968.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of additional chromosome abnormalities in adult patients with Philadelphia chromosome positive acute lymphoblastic leukaemia

Abstract: The clinical and biological significance of additional chromosome aberrations was investigated in a large series of 66 adult patients with Philadelphia (Ph) chromosome positive acute lymphoblastic leukaemia (ALL). Additional chromosome changes were observed in 71% of the cases. 9p abnormalities were identified in 26%, and monosomy 7 as well as hyperdiploid karyotypes 50 were both found in 17% of cases. 9p anomalies were characterized by a low complete remission (CR) rate (58%) and an extremely short median rem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
57
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 0 publications
12
57
0
Order By: Relevance
“…Even in this patient, however, Ph + /hyperdiploid clones were undetectable following induction chemotherapy, and disease relapse appeared to originate from subclones that were Ph + , but not hyperdiploid. These results are similar to those reported by Rieder et al 9 , who detected high hyperdiploidy in up to 17% of adults with Ph + ALL. In their series, patients with the Ph + /hyperdiploid karyotype achieved complete remission more readily than patients who did not have an additional hyperdiploid karyotype, although the duration of remission and overall survival was similar in the two groups.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Even in this patient, however, Ph + /hyperdiploid clones were undetectable following induction chemotherapy, and disease relapse appeared to originate from subclones that were Ph + , but not hyperdiploid. These results are similar to those reported by Rieder et al 9 , who detected high hyperdiploidy in up to 17% of adults with Ph + ALL. In their series, patients with the Ph + /hyperdiploid karyotype achieved complete remission more readily than patients who did not have an additional hyperdiploid karyotype, although the duration of remission and overall survival was similar in the two groups.…”
Section: Discussionsupporting
confidence: 82%
“…Data from Thomas et al 8 have also suggested an improved outlook for Ph + ALL patients with the hyperdiploid karyotype compared to those with other karyotypic abnormalities, although the differences in survival did not approach significance. Both these studies 8,9 have indicated the genetic heterogeneity of Ph + ALL in adults that could potentially translate into variable outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…As far as concerns t-HeH patients with t(9;22), it has been suggested that they either have a more favorable survival and/or treatment response compared with t(9;22)-positive near-diploid ALL 20,21 or the same dismal outcome as all other patients with this translocation. 22,23 The fact that all six t-HeH with t(9;22) in our Nordic cohort achieved complete remission and all but one remain alive would rather agree with the former view ( Table 2; Online Supplementary Table S1). Obviously, larger series are needed to address this clinically important issue, and this is something that will require international collaboration due to the rarity of t-HeH in pediatric patients.…”
Section: In Cases With 51-67 Chromosomes; 2 Data Missing For Some Varsupporting
confidence: 68%
“…40 Similarly, although no molecular data on p16/p15 gene status were reported, 9p deletions were present in 17/66 (26%) adults with Philadelphia chromosomepositive ALL. 41 At this point in time, almost all of the translocations that are observed in Ͼ1% of ALLs and AMLs have been cloned, the involved genes have been identified, and their biochemical functions are under intensive study. 3 To date, p16 and p15 are the only TSGs identified that are inactivated in a significant percentage of leukemias.…”
Section: Resultsmentioning
confidence: 99%